Alpha-Glucosidase Inhibitory Diterpenes from Euphorbia antiquorum Growing in Vietnam - Tran, Cong-Luan (Molecules, 2021)
Bioactive-guided phytochemical investigation of Euphorbia antiquorum L. growing in Vietnam led to the isolation of five ent-atisanes, one seco-ent-atisane, and one lathyrane (ingol-type). The structures were elucidated as ent-1α,3α,16β,17-tetrahydroxyatisane (1), ethyl ent-3,4-seco-4,16β,17-trihydroxyatisane-3-carboxylate (2), ent-atisane-3-oxo-16β,17-acetonide (3), ent-3α-acetoxy-16β,17-dihydroxyatisane (4), ent-16β,17-dihydroxyatisane-3-one (5), calliterpenone (6), and ingol 12-acetate (7). Their chemical structures were unambiguously determined by analysis of one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) and high resolution mass spectrometry, as well as by comparison with literature data. Among them, 1 is a new compound while 2 is an ethylated artifact of ent-3,4-seco-4,16β,17-trihydroxyatisane-3-carboxylic acid, a new compound. Isolates were evaluated for alpha-glucosidase inhibition. Compound 3 showed the most significant inhibitory activity against alpha-glucosidase with an IC(50) value of 69.62 µM. Further study on mechanism underlying yeast alpha-glucosidase inhibition indicated that 3 could retard the enzyme function by noncompetitive.